2017
DOI: 10.1515/ngoe-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Greenfield and Brownfield Investments and Economic Growth: Evidence from Central and Eastern European Union Countries

Abstract: Global foreign direct investment flows in terms of greenfield and brownfield investments have increased during the recent three decades resulting from the accelerating globalization. The considerable increases in the flows of foreign direct investment have many eventualities for the national economies. This study investigates the mutual effects among greenfield and brownfield (mergers and acquisitions) investments and economic growth in Central and Eastern European Union countries during the 2003-2015 period e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 21 publications
2
31
0
5
Order By: Relevance
“…Not least, the policies concerning sustainable development goals should be promoted. In this vein, greenfield and brownfield investments may lessen unemployment, while increasing incomes, public and private consumption, capital accumulation and productivity [89]. As well, infrastructure should be improved to guarantee that FDI which is acquired manifest an increased gain to the entire economy.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Not least, the policies concerning sustainable development goals should be promoted. In this vein, greenfield and brownfield investments may lessen unemployment, while increasing incomes, public and private consumption, capital accumulation and productivity [89]. As well, infrastructure should be improved to guarantee that FDI which is acquired manifest an increased gain to the entire economy.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…58 Thus, researchers found that establishing these under-utilized sites may positively influence economic growth. 59,60…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, in GFI, the construction of new production facilities may also be accompanied by building new offices, distribution hubs and living dorms. 60 Firms prefer GFI in order to exploit long-term opportunities and leverage their competitive advantages in emerging markets if the country risk is low. 65 Nevertheless, likewise BFI, there is a lack of literature related to the influence of GFI on the adoption of green technology or environmental health.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Plyno lauko investicija yra naujo ūkinio komercinio vieneto sukūrimas, pastatymas ir paleidimas veikti tokioje teritorijoje, kurioje iki tol nebuvo vykdoma jokia veikla ir nebuvo sukurta jos infrastruktūra. Bayar (2017) vykdyto tyrimo rezultatai atskleidė, kad tiek plyno lauko, tiek urbanistinės dykros teritorijų investicijos turi teigiamą įtaką ekonomikos augimui. Svarbu pažymėti, kad ne visuomet urbanistinės dykros teritorijos atnaujinimo pramoninei veiklai sąnaudos yra mažesnės už pramoninės zonos įrengimą plyno lauko teritorijoje.…”
Section: Pramoninių Parkų Klasifikacijaunclassified